2023
DOI: 10.1021/acs.organomet.2c00659
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Hydrophosphination of Terminal Alkynes with Diphenylphosphine Oxide in the Presence of Tetraphenyldiphosphine Monoxide

Abstract: In this study, the Pd(OAc) 2 -catalyzed hydrophosphination of terminal alkynes was investigated in detail by using various diphosphines, which have a P−P bond, and the detailed mechanistic insights led to the successful development of a novel Pd-catalyzed hydrophosphination of terminal alkynes using Ph 2 P(O)H as both the phosphorus and hydrogen source. This catalytic transformation was successfully promoted in the presence of catalytic Ph 2 P(O)−PPh 2 , and the corresponding alkenylphosphine oxide was obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…[20] Based on this background, we have energetically developed straightforward synthetic methods of phosphorus-heteroatom compounds and their application to the functionalization of carbon-carbon unsaturated compounds via radical reactions and transition-metal-catalyzed reactions. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] In particular, we have found that diphosphines containing phosphorusphosphorus single bonds can efficiently react with organic dichalcogenides to form the corresponding phosphorus-chalcogen interelement compounds. [32] Among a variety of diphosphines, tetraphenyldiphosphine disulfide, Ph 2 P(S)-P(S)Ph 2 1, is quite stable to air and moisture.…”
Section: Introductionmentioning
confidence: 99%
“…[20] Based on this background, we have energetically developed straightforward synthetic methods of phosphorus-heteroatom compounds and their application to the functionalization of carbon-carbon unsaturated compounds via radical reactions and transition-metal-catalyzed reactions. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] In particular, we have found that diphosphines containing phosphorusphosphorus single bonds can efficiently react with organic dichalcogenides to form the corresponding phosphorus-chalcogen interelement compounds. [32] Among a variety of diphosphines, tetraphenyldiphosphine disulfide, Ph 2 P(S)-P(S)Ph 2 1, is quite stable to air and moisture.…”
Section: Introductionmentioning
confidence: 99%